Interview with Claudia Amigo Pino: Archives and Theories in Circulation (El Hilo de la Fabula, 2024)
This interview with Claudia Amigo Pino (University of São Paulo) focuses on her journey as a researcher to establish points of contact about working with archives, in this case, the one that involves Roland Barthes' unpublished classes taught between the  '60s and '70s at the École Des Hautes Études en Sciences Sociales and whose results are found in Apprendre et Désapprendre. Les séminaires de Roland Barthes (1962-1977) (Academy, 2022). The questions that drive the dialogue recover key points from her book, as well as the avatars of working on a foreign archive.
Keywords: archive; roland barthes; literary criticism; Didactics